CFD simulation of an alfa-stirling engine to study the geometrical parameters on the engine performance - Teixeira, J. Carlos (2019)
An alpha-Stirling configuration was modelled using a Computational Fluid Dynamic (CFD), using ANSYS® software. A Stirling engine is an externally heated engine which has the advantage of working with several heat sources with high efficiencies. The working gas flows between compression and expansion spaces by alternate crossing of, a low temperature heat exchanger (cooler), a regenerator and a high temperature heat exchanger (heater). Two pistons positioned at a phase angle of 90 degrees were designed and the heater and cooler were placed on the top of the pistons. The motion of the boundary conditions with displacement was defined through a User Defined Function (UDF) routine, providing the motion for the expansion and compression piston, respectively. In order to define the temperature differential between the engine hot and the cold sources, the walls of the heater and cooler were defined as constant temperatures, whereas the remaining are adiabatic. The objective is to study the thermal behavior of the working fluid considering the piston motion between the hot and cold sources and investigate the effect of operating conditions on engine performance. The influence of regenerator matrix porosity, hot and cold temperatures on the engine performance was investigated through predicting the PV diagram of the engine. The CFD simulation of the thermal engine's performance provided a Stirling engine with 760W of power output. It was verified that the Stirling engine can be optimized when the best design parameters combination are applied, mostly the regenerator porosity and cylinders volume, which variation directly affect the power output.